Geotechnical and microstructural properties of cement-treated laterites stabilized with rice husk ash and bamboo leaf ash - Emeka Segun Nnochiri; Olumide Moses Ogundipe; Samuel Akinlabi Ola (Acta Polytechnica, 2021)
This study investigated the geotechnical and microstructural properties of cement-treated laterites stabilized with rice husk ash and bamboo leaf ash. In going about the tests, the soil sample was subjected to compaction, California Bearing Ratio (CBR) and preliminary tests; such as specific gravity, particle size distribution and Atterbergs limits to determine its index properties. Thereafter, the soil sample was mixed with cement at varying proportions of 0–12% at 2% intervals and also, separately mixed with bamboo leaf ash (BLA) and rice husk ash (RHA) in proportions of 0–16% at 2% intervals. The mixes at each stage were subjected to compaction, Atterberg limits and CBR tests. The highest values were 66.7% and 54.8% for unsoaked and soaked CBR at 6% cement+8% BLA and 78.5% and 63.8% for unsoaked and soaked CBR at 8% cement+8% RHA. Samples at these optimal CBR values were subjected into Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) tests. Results showed that new compounds were formed and there were changes in the microstructural arrangements. It can therefore be concluded that pozzolanic and cement hydration reactions actually took place in the course of stabilization.